Motivasi Kerja, Tingkat Pendidikan, Kepemimpinan, dan Lingkungan Kerja Terhadap Kinerja Karyawan PT BPR Bank Boyolali - Titik Purwani; Budi Istiyanto (Jurnal Ekonomi Akuntansi dan Manajemen, 2022)
The aim of this study was to determine the impact of work motivation, level of education, leadership and work environment on the performance of employees at PT BPR Bank Boyolali (PERSERODA). The subject of the study were employees of PT BPR Bank Boyolali. In this example, the saturation technique was used on a sample of 88 people. The independent variables in this study are work motivation (X1), educational level (X2), leadership (X3) and work environment (X4), while the related variable (Y) is employee productivity. The type of research used was quantitative research with the use of survey methods. The data analysis used included data tool testing, classical acceptance tests, multiple linear regression tests, hypothesis testing, and deterministic analysis. Looking at the results of the analysis processed with the use of IBM SPSS 26, it can be seen that the level of education, leadership and work environment have a significant impact on employee performance, motivation to work has no significant impact on employee performance, companies must pay attention to motivation to work, level of education , leadership and performance. The work environment at PT BPR BANK BOYOLALI (PERSERODA) is conducive to employee productivity. The aim of this study was to determine the impact of work motivation, level of education, leadership and work environment on the performance of employees at PT BPR Bank Boyolali (PERSERODA). The subject of the study were employees of PT BPR Bank Boyolali. In this example, the saturation technique was used on a sample of 88 people. The independent variables in this study are work motivation (X1), educational level (X2), leadership (X3) and work environment (X4), while the related variable (Y) is employee productivity. The type of research used was quantitative research with the use of survey methods. The data analysis used included data tool testing, classical acceptance tests, multiple linear regression tests, hypothesis testing, and deterministic analysis. Looking at the results of the analysis processed with the use of IBM SPSS 26, it can be seen that the level of education, leadership and work environment have a significant impact on employee performance, motivation to work has no significant impact on employee performance, companies must pay attention to motivation to work, level of education , leadership and performance. The work environment at PT BPR BANK BOYOLALI (PERSERODA) is conducive to employee productivity. Keywords: Work Motivation, Level of education, Leadership, Work environment, Employee performance.